PENGARUH PENGGUNAAN TURBOCHARGER DENGAN INTERCOOLER TERHADAP PERFORMANSI MOTOR BAKAR DIESEL - Mahadi Mahadi (Jurnal Dinamis, 2010)
AbstractThe use of turbochargers with intercooler is to increase the engine power (30-80%), diesel engines with turbochargers can work more efficiently, if the engine has to work at an altitude of more than 1500 meters above sea level, the turbocharger is of significant importance in the effort to overcome losses caused by power by reduced atmospheric air density at the location. Power will increase by 66.1% with a turbocharger and intercooler uses the rotation 2500 rpm, with the number of cylinders and the dimensions of the same machine. Effective pressure - average increase of 66.4% at 2300 rpm with the spin machine that same.Torsi dimensions for motor diesel fuel was also increased by 60.8% at 2100 rpm with dimensional rotation engine specific fuel sama.Consumtion also decreased by 5.20% at 2100 rpm rotation for internal combustion engine with turbocharger and intercooler this. Power indicator on these diesel motor fuel increased by 62.6%. With this result may be said that the use of a turbocharger and intercooler is very efficient and very influential on the performance of the diesel engine. Keywords : turbocharger, intercooler and performansi